Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Ask your questions and receive precise answers from experienced professionals across different disciplines. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve for t
-t=9(t-10)
t=


Sagot :

-t=9(t-10)
-t=9t-90
90=9t+t
90=10t
90/10=t
9=t

Final Answer: [tex]t = 9[/tex]

Steps/Reasons/Explanation:

Question: Solve for [tex]t[/tex]. [tex]-t=9(t-10)[/tex].

Step 1: Expand.

[tex]-t = 9t - 90[/tex]

Step 2: Subtract [tex]9t[/tex] from both sides.

[tex]-t - 9t = -90[/tex]

Step 3: Simplify [tex]-t - 9t[/tex] to [tex]-10t[/tex].

[tex]-10t = -90[/tex]

Step 4: Divide both sides by [tex]-10[/tex].

[tex]t = \frac{-90}{-10}[/tex]

Step 5: Two negatives make a positive.

[tex]t = \frac{90}{10}[/tex]

Step 6: Simplify [tex]\frac{90}{10}[/tex] to [tex]9[/tex].

[tex]t = 9[/tex]

~I hope I helped you :)~